2010
DOI: 10.33961/jecst.2010.1.1.039
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Electrochemical Performance of 1.5 V and 3.0 V-Class Primary Film Batteries for Radio Frequency Identification (RFID)

Abstract: 1.5 V and 3.0 V-class film-type primary batteries were designed for radio frequency identification (RFID) tag. Efficient fabrication processes such as screen-printings of conducting layer (25 µm), active material layer (40 µm for anode and 80 µm for cathode), and electrolyte/separator/electrolyte layer (100 µm), were adopted to give better performances of the 1.5 V-class film-type Leclanché primary battery for battery-assisted passive (BAP) RFID tag. Lithium (Li) metal is used as an anode material in a 3.0 V-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The internal resistance values are also higher with the coplanar battery architecture. This can be related to the extended distance of the electrodes defined by the gap width of at least 1.0 mm which in the field of stack-type batteries is essentially reduced to the separator thickness, usually being in the range of 0.1-0.2 mm [16,22,23,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The internal resistance values are also higher with the coplanar battery architecture. This can be related to the extended distance of the electrodes defined by the gap width of at least 1.0 mm which in the field of stack-type batteries is essentially reduced to the separator thickness, usually being in the range of 0.1-0.2 mm [16,22,23,25].…”
Section: Introductionmentioning
confidence: 99%
“…Various conventionally available electrochemical battery systems have been realised at least in laboratory scale by means of a printing process. While individual research activities can be observed in the area of printed secondary Ni|MH [9][10][11], primary Zn|Ag 2 O [12,13], primary Zn|O 2 [14,15] and secondary Li|Ion batteries [16][17][18], the primary zinc-carbon (Zn|MnO 2 ) battery system [7,9,[19][20][21][22][23][24] seems to be the most attractive battery chemistry for printing applications. The Zn|MnO 2 battery can be operated with an alkaline potassium hydroxide electrolyte (KOH) as well as with acidic electrolytes based either on ammonium chloride (NH 4 Cl) or zinc chloride (ZnCl 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The range of areal capacities declined from 2.0-2.8 mAh cm −2 (0.2 mA CC) to 0.8-1.6 mAh cm −2 (0.4 mA CC). However, the most efficient batteries of this study may compete with reported areal capacities of screenprinted Zn|MnO 2 batteries (1.9-3.1 mAh cm −2 ) [30,31,35,45,46], printed lithium-ion batteries (1.8-2.5 mAh cm −2 ) [11,47] and printed zinc-air batteries (0.5-2.0 mAh cm −2 ) [48,49].…”
Section: Conflict Of Interestmentioning
confidence: 73%